An appraisal of the proposal for BRAC's education programme: phase III, 22nd August-12th September 1998 - Bailey, Miriam; Reeves, Barry; Ryan, Anne; Smith, Brigid (© BRAC, 2016)
1. Introduction 2. Long term vision planning 3. Institutional management and development 4. Significant changes in phase III 5. The budget 6. List of people and groups consulted.